STUDENTS’ PERCEPTIONS OF THE USE OF POWER POINT SLIDE SHOW FOR TEACHING ENGLISH SUBJECT - Maliqul Hafis (IKIP PGRI Pontianak, 2013)
The main purpose of this research is to find out the students’ perceptions of the use Power Point slide show for teaching English in the classroom. The population was the students of Madrasah TsanawiyahNegeriRasau Jaya in academic year 2012/2013 with a total number of 276 students. Then, the researcher chose seventh grade of MTs NegeriRasau Jaya students as the sample for this study. The tools used in collecting the data were questionnaire and interview technique (mixed method). The result of data analysis is first, some students of seventh grade of MTs.NegeriRasau Jaya perceived that the use of PowerPoint slide show had positive side, it was proved from the result of mean score from all participants reported that 4, 03 of the students perceived PowerPoint slide show is positive to be used because PowerPoint slide show can improve students’ grade. Also interactiononand communication between teachers and students became more interesting, joyful and relax. The second, there were some of students of seventh grade of MTs.NegeriRasau Jaya also perceived that the use of PowerPoint slide show had negative side, it was proved from the result of mean score from all participants that the mean score is 3, 96. It means that the students are neither agree nor disagree to the statements because PowerPoint slide show cannot be used in any kind of situation especially when there was not electricity this media cannot be used for teaching English in the classroom.Keywords: Students’ Perceptions, Power Point, Teaching English